The relationship between the leadership behaviour of coaches and team cohesion in University basketball teams - Shi, W. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Cohesion is seen as a very important factor in team performance and many coaches are trying to enhance the cohesion of their teams. Terry (1984) revealed that the personality and leadership behaviours of a coach can have an important effect upon players` performance and satisfaction. The purpose of this research was to reveal the relationship between a coach's leadership behaviours and the cohesion of basketball teams. Cohesion has been defined as "a dynamic process which is reflected in the tendency for a group to stick together and remain united in the pursuit of its goals and objectives". Carron's conceptual model of cohesion includes task cohesion and social cohesion. The Group Environment Questionnaire (GEQ) (Carron, et al., 1985) was used to examine the cohesion of teams and The Leadership Scale for Sports (LSS) (Chelladurai, 1994) was used to measure the following five dimensions of coaching behavior: training and instruction, democracy, autocracy, social support and rewarding systems. Many studies have used the LSS and GEQ to measure behavior independently, but few have combined them to examine the relationship between leader behaviour and cohesion in sporting teams. It is hypothesized that a significant relationship exists between team cohesion (social cohesion and task cohesion) and the coaching behaviours (training and instruction, social support, democratic and rewarding behaviour). The purpose of this study was to reveal the relationship between cohesion of basketball teams and the relevant coaches` leadership behaviours at universities in Shanghai. Methods The perceived and preferred versions of the Chelladurai`s Leadership Scale for Sports (1994) revised by scholars in Taiwan served as the measure of leadership behaviour. The Group Environment Questionnaire (GEQ) served as the measure of cohesion. GEQ consists of four parts: individual attractions to the group—task; individual attractions to the group—social; group integration—task; and group integration—social. Correlation and one-way MANOVA were applied to analyse the results. One hundred players and twenty coaches of basketball teams in the universities in Shanghai were examined. Results / Discussion Teams in which `training and instruction behaviour`, `social support behaviour` and `democratic behaviour`, were preferred by the players were significantly associated with improved task cohesion and social cohesion (p<.05). `Training and instruction behaviour`, `social support behaviour` and `democratic behaviour` as perceived by the basketball players are significantly related to the task cohesion of the team (p<.01). `Social support behaviour` as perceived by the players was also significantly related to the teams` social cohesion (p<.05). The basketball players classified as highly cohesive perceive and prefer more of their coaches` `Training and instruction behaviour`, `social support behaviour` and `democratic behaviour` than the basketball players classified as having less cohesion. The results of the research indicate that if the basketball coaches are to promote the team`s cohesion, they will should strengthen their `training and instruction behaviour`, `social support behaviour` and `democratic behaviour`.